Incidence of atrial fibrillation and its related factors in patients over 40 years old with secondary atrial septal defect before and after interventional closure - ZHU Tao; XU Xiang; HUANG Haiyun; WAN Chen; LIU Feng (陆军军医大学学报, 2022)
Objective To assess the incidence of atrial fibrillation (AF) in patients with atrial septal defect (ASD)before and after interventional closure, and analyze the related risk factors. Methods A retrospective study was carried out in the ASD patients over 40 years old undergoing interventional closure in our hospital from August 2014 to June 2021. According the presence of AF or not before interventional closure, they were divided into ASD plus AF group and ASD plus sinus rhythm group. Based on the occurrence of new-onset AF or not after interventional closure, they were also assigned into new-onset AF group and sinus rhythm group. The related factors were analyzed by comparing those in the ASD plus AF group, new-onset AF group and the sinus rhythm groups. Results A total of 280 patients were recruited in this study, including 75 males and 205 females, at a mean age of 40~83(54.51±10.02) years. The incidence of AF in ASD patients before interventional closure was 16.07% (45/280). Of the 235 patients who were in sinus rhythm before interventional closure, 15 (6.38%) patients developed new-onset AF during the follow-up of 42.40±23.98 months. In comparison to the patients who did not have AF, the patients who had AF before interventional closure were significantly older (P < 0.001), and with NYHA functional class Ⅱ or worse (P=0.004), dilated both left and right atriums (P < 0.001) and higher right ventricular pressure (P < 0.001). Compared to the patients with sinus rhythm after interventional closure, those with new-onset AF were older (P < 0.001), and with dilated left atrium (P=0.008), right atrium (P=0.003) and right ventricle (P=0.042), but a lower left ventricular ejection fraction (LVEF, P=0.004). Logistic regression analysis showed that older age, dilated left atriums, NYHA functional class ≥Ⅱ and elevated right ventricular pressure were risk factors of AF, and age was the main risk factors of new-onset AF in ASD patients after interventional closure. Conclusion The incidence of AF is quite high in ASD patients over 40 years old no matter before or after interventional occlusion. Older age, dilated atriums, worse NYHA functional class and higher right ventricular pressure may be the risk factors for the occurrence of AF, and among them, age is the main risk factor of new-onset AF.